Effect of lockdown on food security during the COVID-19 pandemic in the Philippines two months after implementation - Villanueva, Jessica D.; Austria, Jonathan D.; Faronilo, Kendrick Mico; Sunga-Lim, Aywin Rosette; Replan, Enrico L.; Sevilla-Nastor, Janice B.; Abuyan, Renante N.; Peyraube, Nicolas (2022)
The alarming presence of COVID-19 challenged the United Nations’ (UN) Sustainable Development Goal 2 and made the World Health Organization (WHO) declare a public health emergency of international concern. Imposed lockdowns disrupted the supply and demand chain of the food systems, hence affecting food security. This research would like to know and assess the early effect (two months after the lockdown) of the enhanced community quarantine on food security in the Philippines. An online survey was employed participated by 331 household representatives using a survey instrument containing food security assessment, household sociodemographic characteristics, behavioral responses covering food purchase and consumption behavior, and emergency measure adoption. Statistical tests were applied: Mann-Whitney U test to know the behavioral response of the food secure vs. food insecure households, as well as the phi coefficient and Cramer’s V test to determine and assess the parameters that plays important role in food security during this period. Results showed that 73% of the respondents were food insecure. The early effect of the lockdown was seen in the behavioral responses, significant differences between food secure and insecure households were found in age, income, and food purchase behavior. Parameters associated with food security are age, income, food allocation, expectations on the livelihood impact and change in expenditure, and the adoption motivations in practicing backyard gardening. The stress evaluation revealed that while Filipinos tried to cope, an increased level of anxiety was experienced. The need for clear measures in terms of preparedness in any pandemic situation was heightened. These findings are significant in providing benchmark information on food security during a pandemic.
Keywords: Food security; COVID-19 pandemic